Assessment of the utility of Yale observation scale as a predictor of bacteremia in children aged 3 months to 36 months - Sudhakar, P.; Ajitha, P. (International Journal of Contemporary Pediatrics, 2019)
Background: The Yale observation scale (YOS) is an illness severity helps to diagnose bacteremia based on simple noninvasive clinical signs and symptoms. The aim of the present study was to assess the utility of YOS as a predictor of bacterial infection in febrile children aged 3 to 36 months. Methods: This prospective observational study was conducted on 200 children aged 3 to 36 months presenting with fever, at the Institute of Child Health and Hospital for Children during the period from April 2016 to September 2016. Rectal temperature was taken for all children. Clinical examination was done as required based on the YOS and scores were given accordingly at the time of initial presentation of the child before invasive investigations. All the observation was assessed statistically and receiver operating characteristics (ROC) curve was performed to analyze the sensitivity of the YOS. Results: Highly significant correlation (p=0.0001) was found to exist between the age of the child, duration of the fever, higher body temperature >104, WBC count, ANC and improved condition of patient with higher YOS. ROC curves showed that the sensitivity and specificity of YOS at the best cut off value of 14.5 was found to be 97% and 79.6% respectively. Conclusions: YOS is very good tool for predicting bacteremia in young febrile children based on simple non-invasive clinical signs and symptoms. The findings ruled out by YOS aids in the immediate and early management of bacterial infections before the arrival of the results of the biochemical diagnostic tests.